2015
DOI: 10.1039/c4nj01687d
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient and reusable MCM-41-immobilized bipyridine copper(i) catalyst for the C–Se coupling of organoboronic acids with diaryl diselenides

Abstract: A heterogeneous copper-catalyzed cross-coupling reaction of diaryl diselenides with organoboronic acids for the synthesis of diorganyl selenides has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…On the basis of these results and in accordance with previous reports [ 66 , 67 ], a plausible reaction pathway is illustrated in Scheme 6 . In this pathway the catalyst cycle begins with the generation of species A through the reaction between CuI and boronic acid [ 66 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the basis of these results and in accordance with previous reports [ 66 , 67 ], a plausible reaction pathway is illustrated in Scheme 6 . In this pathway the catalyst cycle begins with the generation of species A through the reaction between CuI and boronic acid [ 66 ].…”
Section: Resultssupporting
confidence: 91%
“…Subsequently, this specie reacts with diorganyl dichalcogenide to afford the desired product and the intermediate B . The specie B is then oxidized to give the Cu(II) intermediate C [ 66 , 67 ]. In the next step, another equiv.…”
Section: Resultsmentioning
confidence: 99%
“…These Cu(II)‐based catalysts are readily available, of low cost, stable in air and can be easily handled in comparison to other transition metal catalysts . Frequently, copper complexes with suitable and stable ligands including bipyridine, dabco, triazole dendrimer, triazine‐based polyethyleneamine dendrimer and amidoxime have been supported on various solid supports to efficiently perform organic reactions. Schiff base catalysts supported on various solid supports have also been applied for a range of organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Up to the present time, some functionalized MCM‐41‐immobilized copper complexes have been synthesized and successfully used in different organic reactions . It was demonstrated that the stability and activity of copper‐based nanocatalysts is meaningfully enhanced after their formation on MCM‐41.…”
Section: Introductionmentioning
confidence: 99%